Instant and quantitative epoxidation of styrene under ambient conditions over a nickel(ii)dibenzotetramethyltetraaza[14]annulene complex immobilized on amino-functionalized SBA-15. Issue 58 (24th September 2020) - Abboud, Mohamed; Al-Zaqri, Nabil; Sahlabji, Taher; Eissa, Murad; Mubarak, Ahmed T.; Bel-Hadj-Tahar, Radhouane; Alsalme, Ali; Alharthi, Fahad A.; Alsyahi, Amjad; Hamdy, Mohamed S.
Abstract : Immediate and quantitative epoxidation of styrene under ambient conditions catalyzed by new nanocatalyst obtained by immobilizing nickel(ii )dibenzotetramethyltetraaza[14]annulene in amino-functionalized SBA-15. Abstract : Nickel(ii )dibenzotetramethyltetraaza[14]annulene complex (Nitmtaa) was synthetized and immobilized on post amino-functionalized SBA-15 (N-SBA-15) to obtain a stable and reusable nanocatalyst named as Nitmtaa@N-SBA-15. Here (3-aminopropyl)triethoxysilane (APTES) was first grafted on the surface SBA-15, then Nitmtaa was added and coordinated on the silica surface via APTES amine groups. The structure and morphology, and thermal stability of the prepared nanocatalyst was investigated using SEM, HR-TEM, BET, FT-IR, powder XRD, and TGA. HR-TEM and XRD results revealed a high dispersion of Nitmtaa on the SBA-15 surface. The catalytic activity of this nanocatalyst was evaluated in the epoxidation of styrene, under ambient conditions, using meta -chloroperoxybenzoic acid ( m -CPBA) as the oxygen donor. This nanocatalyst showed an immediate and quantitative epoxidation of styrene with high turn-over-frequency ∼31.58 s −1 . Moreover, the superior catalytic activity and high stability of Nitmtaa@N-SBA-15 could be maintained after four successive cycles. A possible reaction mechanism is also proposed.